Computer-assisted engineering of programmed drug releasing multilayer nanomedicine via indomethacin-mediated ternary complex for therapy against a multidrug resistant tumor. (1st October 2019) - Che, Ling; Liu, Zhirui; Wang, Dong; Xu, Chunmei; Zhang, Chengyuan; Meng, Jin; Zheng, Jun; Yuan, Hongfeng; Zhao, Guanren; Zhou, Xing
Graphical abstract: Abstract: Nanomedicine with programmed drug release can give full play to the synergistic effect of multi-component system in complicated tumor environment. However, the construction of these programmed drug delivery systems often depends on the sophisticated materials design and synthesis. In this study, we successfully designed an indomethacin (IND)-mediated ternary complex system based on a PEG cleavable polyethyleneimine (PEI), indomethacin (IND) and benzene ring containing chemotherapeutic drugs (such as paclitaxel (PTX), doxorubicin and docetaxel). Based on the difference of hydrophobicity in these components, these components were one-pot self-assembled into drug-loaded IND mediated PEGylation cleavable nanoassemblies (IPCNs) in multilayer structure. In drug-loaded IPCNs, PEG fragments, PEI/IND, and chemotherapeutic drug were respectively distributed from the out layer to core of nanomedicine. When drug-loaded IPCNs reached tumor site through EPR effect, the PEG fragment would firstly responsively release to the acidic tumor microenvironment to expose the intermediate layer of drug-loaded IPCNs that composed by mixture of PEI and IND for increasing the surface potential to promote the uptake by tumor cells. After entering cells, IND would be released faster than chemotherapeutic drug encapsulated in core to efficiently inhibit the expression of multidrug resistance protein 1 to reverse MDR of tumor cells before chemotherapeutic drug releasing. Contributed by the staged responsively releasing of PEG fragments, IND and encapsulated chemotherapeutic drug, the drug-loaded IPCNs exhibited a superior antitumor efficacy against A549/MDR tumor cells both in vitro and in vivo. Statement of Significance: The way to develop programmed released drug delivery system is commonly relied on complicated material design and synthesis. Herein, under the computer-assist design, we successfully designed a ternary complex derived from indomethacin (IND), paclitaxel (PTX) and a pH-responsive PEGylated polyethyleneimine (PEG-s-PEI), and employed this ternary complex to successfully prepare a high drug loading and multilayer structured nanomedicine of PTX (PTX IPCNs). Contribute by the different location of PTX, IND and PEG-s-PEI in PTX IPCNs, PEG fragments, IND and PTX molecules could programmed release after reaching tumor for perfectly realizing the synergistic anti-tumor effect of tumor targeting, reversal of MDR and chemotherapy. Based on a fusion of these multiple mechanisms, PTX IPCNs showed a superior antitumor efficacy in mice loading A549/MDR tumor.